PENGEMBANGAN BAK UJI UNTUK MEDIA PEMBELAJARAN DALAM PENGUKURAN TORSI RODA TRAKSI - Lisyanto .; E. Namaken Sembiring; M.Sjahrul Annas (Jurnal Keteknikan Pertanian, 2006)
ABSTRACT Measurement of torque and performance of traction wheel is generally employed a device of big soil bin. The device however is not to be employed as a leaming media in the classroom scale. Development the model of soil bin to measure tourque and performance of traction wheel, wich can be used in the classroom, is necessary, in order to gain effective and simplicity for learning systtem. Development of the model can be designed by decreasing the dimension of the bin to be smaller, whereas the main component and the shape of the bin are remaining the same,and by the development are needed, i.e.: 1) type of contact surface made of sandy loam soil, rubber, and iron plate, 2) dynamic loade of wheel of 50 N, 100 N, and 150 N. Model of soil bin that will be developed will has a dimension of 1 m length, 0.4m widht, and 0.8 m height. The model suitable as a media of learning system in classroom scale for exploring the measurement method of torque and performance of traction wheel. The higher the dynamic wheel loads the more increasing the maximum torque. In results of the experiment, rubber give the more higher torque (0.53 N m) than torque resulted by soil (0.34 N m) and iron (0.21 N m). Keyword: soil bin, torque, traction, learning media system